Determining standard criteria for endotracheal suctioning in the paediatric intensive care patient: An exploratory study - Davies, Kylie; Monterosso, L; Leslie, Gavin (Churchill Livingstone, 2011)
This four-phase mixed method study developed an evidence based ‘‘Endotracheal Suction Assessment Tool’’ (ESAT) as a guide for nurses undertaking ‘‘endotracheal tube’’ (ETT) suction within ‘‘Paediatric Intensive Care’’ (PIC). Phase 1 involved a comprehensive literature review to determine the most commonly used criteria for assessing the need for ETT suction. In Phase 2 an ‘‘Endotracheal Suction Questionnaire’’ (ESQ) was developed to survey experienced PIC nurses in Australia and New Zealand regarding their ETT suction decision making process and validity testing of the ESQ. In Phase 3, the ESQ was administered to target group (n = 104). In Phase 4, the empirical evidence generated from this study, based upon the criteria rated by nurses in this study as being most clinically important and essential during the decision making process, determined the ESAT design. Analyses of quantitative results showed a positive correlation between the perceived frequency of use of a criterion and the appropriateness of the assessment. Where a criterion was used less frequently as a clinical indicator for the requirement for ETT suction, participants had a lower regard for this when rating the criterion as a specific single indicator to perform suction. Findings from qualitative data identified six criteria not previously documented within the literature. Further testing and validation of the tool within the PIC setting will determine the clinical viability of the ESAT.